MUHAMMAD IQBAL DAN IDE-IDE PEMIKIRAN POLITIKNYA - Hawi, Akmal (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2016)
Muhammad Iqbal And His Political Ideas. The emergence of the renewal idea of of a figure can not be separated from social conditions wherever they live. Similarly, Muhammad Iqbal with his thoughts has been able to bring influence on political reform in Islam. One of his ideas is the will to establish an islamic state for Muslims in India separated from the Hindus. He believes that Muslims in India is a nation based on the bond of brotherhood among Muslims. From this article it was found that the emergence of this idea is influenced by the decline of the Muslims because of the stagnation in ijtihad. Although Iqbal did not realize his willing during hislifetime, but after 25 years of his death, Iqbal’s struggle finally became real with the establishment of the Islamic state of Pakistan by Muhammad Ali Jinnah. Because of his ideas and struggle, Muhammad Iqbal later is called as the father of Pakistan, because he is actually the designer of the initial establishment of the Islamic state of Pakistan separated from India.